2020
DOI: 10.3390/agronomy10010122
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Engineering in Tropical Cash Crops

Abstract: Tropical and subtropical crops such as coffee, cacao, and papaya are valuable commodities, and their consumption is a seemingly indispensable part of the daily lives of billions of people worldwide. Conventional breeding of these crops is long, and yields are threatened by global warming. Traditional chromosome engineering and new synthetic biology methods could be used to engineer new chromosomes, facilitate the transmission of wild traits to improve resistance to stress and disease in these crops, and hopefu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
(149 reference statements)
0
5
0
Order By: Relevance
“…Meiotic division and gametophytic ploidy are tightly regulated processes at the molecular level, and many of these regulators have been successfully characterized 25 . For instance, mutations in the Arabidopsis thaliana gene DYAD/SWITCH1 (SWI1; At5g51330) functioning in cohesion regulation 28 and its maize and rice homologs, both named AMEI-OTIC1 (GRMZM5G883855 and Os03g44760) 29 , lead to the abrogation of synapsis during meiosis I and rather turn it into a mitotic-like cycle 30 . However, in the Arabidopsis mutants parallel-spindle 1 or Jason, disturbed orientation of the spindle leads to a similar effect 31 .…”
Section: Synapsis Chromosome Segregation and Meiotic Non-reductionmentioning
confidence: 99%
“…Meiotic division and gametophytic ploidy are tightly regulated processes at the molecular level, and many of these regulators have been successfully characterized 25 . For instance, mutations in the Arabidopsis thaliana gene DYAD/SWITCH1 (SWI1; At5g51330) functioning in cohesion regulation 28 and its maize and rice homologs, both named AMEI-OTIC1 (GRMZM5G883855 and Os03g44760) 29 , lead to the abrogation of synapsis during meiosis I and rather turn it into a mitotic-like cycle 30 . However, in the Arabidopsis mutants parallel-spindle 1 or Jason, disturbed orientation of the spindle leads to a similar effect 31 .…”
Section: Synapsis Chromosome Segregation and Meiotic Non-reductionmentioning
confidence: 99%
“…Meiotic division and gametophytic ploidy (see Table 1 ) are tightly regulated processes at the molecular level, and many of these regulators have been successfully characterized [ 38 ]. For instance, mutations in the Arabidopsis thaliana gene DYAD/SWITCH1 ( SWI1 ; At5g51330 ) (see Table 2 ) functioning in cohesion regulation [ 41 ] and its maize and rice homologs, both named AMEIOTIC1 ( GRMZM5G883855 and Os03g44760 ) [ 42 ], lead to the abrogation of synapsis during meiosis I and rather turn it into a mitotic-like cycle [ 43 ]. However, in the Arabidopsis mutants parallel-spindle 1 or Jason , disturbed orientation of the spindle leads to a similar effect [ 43 ].…”
Section: Synapsis Chromosome Segregation and Meiotic Non-reductionmentioning
confidence: 99%
“…For example, Silva et al (2008) investigated the behavior of the boll weevil ( Anthonomus grandis ) when attacking ratooned upland cotton mutants whose morphological characteristics included okra-shaped leaves, frego bracts, and red coloration, and the results clearly showed that the number of eggs laid per red plant with frego bracts was lower than that laid on the other plant types. In addition to the use of transgenic methods to breed insect-resistant cotton, emerging molecular biology technologies, such as gene editing and RNA-interference (RNAi) gene silencing technologies, are being used ( Bolaños-Villegas, 2020 ).…”
Section: Future Studies On Ratoon Cotton For Heterosis Utilizationmentioning
confidence: 99%